2003
DOI: 10.2527/2003.8182041x
|View full text |Cite
|
Sign up to set email alerts
|

Early weaning to reduce tissue mobilization in lactating sows and milk supplementation to enhance pig weaning weight during extreme heat stress1,2

Abstract: This study was conducted to determine the effect of reduced lactation length and supplemental milk replacer (MR) during high ambient temperatures. Thirty nine primiparous and 100 multiparous sows (PIC, Franklin, KY, C-22) were used in a 2 x 2 x 2 factorial arrangement of treatments. Treatments consisted of two lactation room temperatures (21 degrees C [TN] and 32 degrees C [HOT]), two lactation lengths (14 or 19 d), and two parity groups (primiparous, multiparous). Pigs were either: 1) sow-reared to 19 d or 2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
33
2
9

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 35 publications
7
33
2
9
Order By: Relevance
“…This finding is not in compliance with that reported by Spencer et al (2003), i.e. high room temperatures during lactation decrease milk production, piglet growth rate and reproductive performance of the sow.…”
Section: Discussioncontrasting
confidence: 56%
“…This finding is not in compliance with that reported by Spencer et al (2003), i.e. high room temperatures during lactation decrease milk production, piglet growth rate and reproductive performance of the sow.…”
Section: Discussioncontrasting
confidence: 56%
“…Jarvis et al (2006) and Cronin et al (1991) have demonstrated that extended confinement may lead to chronic stress responses. In general, the body reserves of lactating sows are depleted throughout lactation (Spencer et al, 2003) and, it is known that poor body condition may increase the risk of shoulder Animal welfare of nurse sows lesions (Zurbrigg, 2006;Knauer et al, 2007). Thus, we expected a higher incidence of shoulder lesions in nurse sows due to a longer lactation length and thus a higher risk of poor body condition.…”
Section: Discussionmentioning
confidence: 96%
“…For example, supplementing diets with L-carnitine during lactation sows resulted in higher milk yields than the controls for days 11 and 18 of lactation. Highly significant breed difference was found in the amount of milk produced and in the average size of the litter suckled, whereas a significant difference was found in the average litter weight at the end of the suckling period (Allen and Lasley, 1960;King et al, 1997;Ramanau et al, 2004;Spencer et al, 2003).…”
Section: Introductionmentioning
confidence: 86%